Design and mechanical analysis of a 3D-printed biodegradable biomimetic micro air vehicle wing - Salami, E.; Ganesan, P. B.; Ward, T. A.; Viyapuri, R.; Romli, F. I. (Institute of Physics Publishing, 2016)
The biomimetic micro air vehicles (BMAV) are unmanned, micro-scaled aircraft that are bio-inspired from flying organisms to achieve the lift and thrust by flapping their wings. There are still many technological challenges involved with designing the BMAV. One of these is designing the ultra-lightweight materials and structures for the wings that have enough mechanical strength to withstand continuous flapping at high frequencies. Insects achieve this by having chitin-based, wing frame structures that encompass a thin, film membrane. The main objectives of this study are to design a biodegradable BMAV wing (inspired from the dragonfly) and analyze its mechanical properties. The dragonfly-like wing frame structure was bio-mimicked and fabricated using a 3D printer. A chitosan nanocomposite film membrane was applied to the BMAV wing frames through casting method. Its mechanical performance was analyzed using universal testing machine (UTM). This analysis indicates that the tensile strength and Young's modulus of the wing with a membrane is nearly double that of the wing without a membrane, which allow higher wing beat frequencies and deflections that in turn enable a greater lifting performance.